Simulation System of Space-Air-Ground Integrated Micro-Service New Network Architecture in 6G - Junyi YANG; Fandi PEI; Zhaolong XU; Zhenyu XIAO (天地一体化信息网络)
The space-air-ground integrated network is the inevitable trend of 6G development in the future.A set of verifi cation simulation system was designed and set up for the micro-service new network architecture of space-air-ground integrated network in 6G.A four-layer simulation system architecture was proposed, included access user layer, radio unit-distributed unit (RU-DU) layer, NFV case management layer and micro-service network element layer.The whole process of network topology establishment, user registration, session establishment and communication case simulation could be realized, which embodied the function of service-oriented network element.Three basic simulation communication cases, namely communication between users, handover management and session management, were designed, and the feasibility of the new network architecture was verifi ed by the handover management case, which laid the engineering foundation for the iterative evolution of network architecture.